EVIDENCE OF LOCAL GOVERNMENT POLICIES AND THE CHALLENGES FACED (A STUDY OF THE LEGAL AFFAIRS BUREAU OF THE LAMPUNG PROVINCIAL GOVERNMENT) - Eko Budi Sulistio; Simon Sumanjoyo Hutagalung; Ita Prihantika (Utan Kayu Publishing, 2026)
One of the public policy processes that rarely receives attention and is rarely carried out is the public policy evaluation stage. However, this policy evaluation activity is very important because it can assess the success or failure of a public policy implementation. As part of the government, it is appropriate for the Lampung Provincial Government to evaluate each implemented public policy to assess its performance (results and impacts) in solving public problems. The purpose of this study is to determine, describe, and analyze the policy evaluation activities that have been carried out by the Lampung Provincial Government to determine the performance of the policies. This research is a descriptive study with a qualitative approach, where data were collected through in-depth interviews and documentation. The results of the study show that public policies in the form of Regional Regulations (Perda) of Lampung Province in 2023-2024 were subjected to formal evaluation by the central government in the form of a review to determine whether the regulation contradicts the regulations above or not. Meanwhile, no substantive evaluation of these regulations was specifically carried out by the Lampung Provincial Government.